Toward a Variable Stiffness Surgical Manipulator Based on Fiber Jamming Transition - Brancadoro, Margherita; Manti, Mariangela; Grani, Fabrizio; Tognarelli, Selene; Menciassi, Arianna; Cianchetti, Matteo (Frontiers in Robotics and AI, 2019)
Soft robots have proved to represent a new frontier for the development of intelligent machines able to show new capabilities that can complement those currently performed by robots based on rigid materials. One of the main application areas where this shift is promising an impact is minimally invasive surgery. In previous works, the STFF-FLOP soft manipulator has been introduced as a new concept of using soft materials to develop endoscopic tools. In this paper, we present a novel kind of stiffening system based on fiber jamming transition that can be embedded in the manipulator to widen its applicability by increasing its stability and with the possibility to produce and transmit higher forces. The STIFF-FLOP original module has been re-designed in two new versions to incorporate the variable stiffness mechanism. The two designs have been evaluated in terms of dexterity and variable stiffness capability and, despite a general optimization rule did not clearly emerge, the study confirmed that fiber jamming transition can be considered an effective technological approach for obtaining variable stiffness in slender soft structures.